Empiricism as a Branch of Philosophy and Its Influence on the Development of Science and Technology in the Islamic World - Firdaus; Abdul Muid Nawawi (ALSYS, 2026)
Empiricism constitutes a major branch of epistemological philosophy that emphasizes observation, experimentation, induction, and verification as foundations of knowledge; however, its relationship with scientific development in the classical Islamic world requires further systematic examination. This study analyzes the principles of empiricism and their contribution to the advancement of science and technology in the classical Islamic intellectual tradition. Employing a qualitative descriptive-analytical library research design, the study examines primary texts by Western empiricist philosophers, Qur’anic and hadith-based epistemological sources, and the works of classical Muslim scholars, supported by relevant secondary literature. The findings indicate that the core principles of empiricism were reflected in the scientific practices of Ibn al-Haytham, Al-Biruni, Jabir ibn Hayyan, Al-Razi, Ibn Sina, and other Muslim scholars. Their contributions to optics, astronomy, chemistry, medicine, and mathematics demonstrate a systematic reliance on observation, experimentation, and empirical verification rather than speculative reasoning alone. The analysis further shows that Islamic epistemology provides a compatible foundation for empirical inquiry by integrating revelation, reason, and sensory experience. This synthesis enabled Muslim scholars to develop a distinctive scientific tradition characterized by methodological rigor and spiritual orientation. The study concludes that the historical legacy of Islamic empiricism offers a relevant framework for revitalizing contemporary science and technology in the Muslim world. Its principal contribution lies in demonstrating that the renewed application of observation, experimentation, and critical verification within an Islamic epistemological framework may strengthen scientific development while maintaining ethical and theological coherence. Keywords: Classical Islamic Science; Empirical Inquiry; Empiricism; Epistemology; Islamic Intellectual Tradition